Respostas de espécies de gramíneas forrageiras a camadas compactadas de solo - SILVA, GILSON PEREIRA; NOVAIS, ROBERTO FERREIRA DE; NEVES, JÚLIO C. LIMA; BARROS, NAIRAM FÉLIX DE (Revista Ceres, 2015)
.